A high temperature resistant and high conductive tin soldering wire and a preparation method thereof

By introducing dumbbell-shaped nanoAg particles and Ti2SnC nanosheets into the solder wire, a semi-convergent interface is constructed and the flux composition is optimized, the shortcomings of solder wire in terms of high temperature and conductivity are solved, and the conductivity and high temperature resistance of solder materials are significantly improved.

CN118905495BActive Publication Date: 2025-03-04SHENZHEN YUDA TIN IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411229507.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-03-04
Estimated Expiration
2044-09-03

AI Technical Summary

Technical Problem

Existing soldered wires have shortcomings in their high temperature resistance and conductivity, and are difficult to meet the high-performance needs of new energy vehicles, high-speed rail transit and 5G communications.

Method used

High-temperature and high-conductive tin soldering wire composed of tin alloy and flux, the tin alloy consists of dumbbell-shaped nanoAg particles, Ti2SnC nanosheets, Sn powder, Cu powder, La powder and Ce powder. The flux is composed of carbon nanotubes, rosin, polyvinyl alcohol and ethylene glycol loading nanoCu particles. By constructing a semi-convergent interface of Ag3Sn/β-Sn and Ti2SnC/β-Sn, the material's conductive properties and high-temperature resistance are improved.

Benefits of technology

It significantly improves the conductivity and high temperature resistance of solder materials, enhances the mechanical properties and reliability of solder joints, and is suitable for high-power density electronic packaging and 5G communication base stations and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118905495B_ABST
    Figure CN118905495B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of welding materials, and provides a high-temperature resistant and highly conductive tin solder wire and a preparation method thereof, wherein the outer layer of the solder wire is a tin alloy containing dumbbell-shaped nano-Ag particles, Ti2SnC nanosheets and a variety of metal powders, and the inner layer is a special solder flux. The Ag3Sn phase in the alloy is generated in situ by nano-Ag particles and Sn powder at high temperature, uniformly covers the nano-Ag particles, and forms a semi-coherent interface with β-Sn to enhance performance. The solder flux incorporates a variety of components such as carbon nanotubes, rosin, and polyvinyl alcohol loaded with nano-Cu particles to optimize the welding effect. The preparation method is to melt nanomaterials and metal powders to obtain alloys, stir and mix nanoparticles to make solder flux, and then co-extrude the solder wire. The present invention adopts dumbbell-shaped nano-Ag particles to induce the in-situ self-generation technology of Ag3Sn phase, introduces Ti2SnC nanosheets to construct a semi-coherent interface, and combines the synergistic effect of multiple components to comprehensively improve the high temperature resistance, conductivity and comprehensive performance of solder alloys and solders.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of welding materials, and in particular to a high-temperature resistant and highly conductive tin welding wire and a preparation method thereof. Background Art

[0002] In strategic emerging industries such as new energy vehicles, high-speed rail transit, and 5G communications, electronic and electrical equipment are developing towards high-density integration, high power, and high frequency, which puts forward higher requirements on the high temperature resistance and conductivity of welding materials. Taking new energy vehicles as an example, on-board electronic control systems often need to work in high temperature environments for a long time, and the ambient temperature can reach above 150°C. At the same time, the power of motors and power electronic systems continues to rise, and the heat dissipation and conductivity of solder joints under high current conditions face severe challenges. Therefore, it is urgent to develop advanced welding materials that are resistant to high temperatures and highly conductive to meet the harsh working conditions in the above-mentioned fields. This can not only significantly improve the reliability and service life of key components and reduce the failure rate, but also promote the miniaturization and lightweight of equipment and improve system integration. The breakthrough of high-performance welding materials will lay a solid foundation for the leapfrog development of related industries and is of great significance to promoting the implementation of national strategies and the construction of a strong country in science and technology.

[0003] At present, the most widely used welding materials are mainly tin-based solders, especially traditional Sn-Pb eutectic solders. However, traditional tin-based solders still have obvious deficiencies in high temperature resistance and electrical conductivity. On the one hand, the melting point of tin-based solders is low (usually below 250°C), and they are prone to softening and creep under high temperature conditions, which seriously affects the mechanical integrity of the solder joints. On the other hand, the electrical conductivity of tin-based solders is relatively low (about 1 / 6 of the electrical conductivity of copper). Under high current conditions, solder joints are prone to overheating, aggravating creep and oxidation, resulting in increased contact resistance, and further causing power loss and poor heat dissipation. In response to the above deficiencies, academia and industry have carried out a lot of research, mainly focusing on alloy composition optimization and flux modification. By adding precious metals, rare earth elements, intermetallic compounds, etc. to the tin matrix, the melting point and mechanical properties of the solder can be improved to a certain extent. However, due to the low solid solubility between the added elements and the matrix, it is difficult to obtain a significant strengthening effect, and the improvement effect of electrical conductivity is limited. Research on flux mainly focuses on enhancing the adhesion and wettability of flux to improve the fluidity and spreadability of solder during welding, but has little effect on the performance of solder joints. Therefore, a single component optimization strategy is difficult to meet the requirements of advanced electronic and electrical equipment for welding material performance. It is urgent to develop a new material system and preparation process to fundamentally solve the shortcomings of traditional solder in terms of high temperature resistance and conductivity. Summary of the invention

[0004] (1) Technical issues solved

[0005] The purpose of the present invention is to provide a high temperature resistant and highly conductive tin solder wire and a preparation process, so as to solve the problem that the current tin solder wire has insufficient high temperature resistance and conductivity.

[0006] (2) Technical solution

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] The utility model relates to a high temperature resistant and high conductive tin soldering wire, which is composed of a tin alloy of an outer layer and a soldering flux of an inner core.

[0009] The tin alloy is prepared from the following components as raw materials by weight: 3-7 parts of dumbbell-shaped nano-Ag particles, 2-5 parts of Ti2SnC nanosheets, 80-95 parts of Sn powder, 1.2-3.5 parts of Cu powder, 0.001-0.005 parts of La powder and 0.002-0.006 parts of Ce powder.

[0010] The tin alloy contains Ag3Sn phase and β-Sn phase.

[0011] The Ag3Sn phase is formed in situ by in-situ self-generation of dumbbell-shaped nano-Ag particles and Sn powder during high-temperature smelting.

[0012] The Ag3Sn phase is evenly distributed on the surface of dumbbell-shaped nano-Ag particles, with a thickness of 2-6nm.

[0013] The Ag3Sn phase forms a semi-coherent interface with the β-Sn in the tin alloy; and the Ti2SnC nanosheet forms a semi-coherent interface with the β-Sn.

[0014] The soldering flux is prepared from the following components by weight: 3-8 parts of carbon nanotubes loaded with nano Cu particles, 15-25 parts of rosin, 10-16 parts of polyvinyl alcohol, 4-9 parts of ethylene glycol, and 6-11 parts of organic acid.

[0015] Further, the preparation scheme of the dumbbell-shaped nano Ag particles is as follows: 5 to 10 parts of 0.01mol / L AgNO3 solution and 4 to 9 parts of 0.01mol / L trisodium citrate solution are mixed evenly to form a seed solution for standby use. Then, 4 to 10 parts of 0.01mol / L sodium borohydride, 2 to 6 parts of 0.01mol / L AgNO3 and 3 to 8 parts of 0.01mol / L ascorbic acid are sequentially added into 20 parts of 0.08mol / L hexadecyltrimethylammonium bromide aqueous solution to obtain a growth solution, and then 2 to 5 parts of the seed solution are added to the growth solution, and then the pH value of the growth solution is adjusted to 11 with 0.2mol / L NaOH solution, after stirring for 2 to 4h, the solution is filtered, and the filter residue is washed three times with deionized water, and then dried in a vacuum drying oven at room temperature to obtain dumbbell-shaped nano Ag particles.

[0016] Furthermore, the average length of the dumbbell-shaped nano-Ag particles is 5 to 12 nm.

[0017] Furthermore, the preparation method of the Ti2SnC nanosheets is as follows: by weight, the blocky Ti2SnC is crushed with a crusher, and then the Ti2SnC powder is obtained by ball milling and then sieved through a 500-mesh sieve, followed by washing once with a 25wt% HCl solution and 25wt% aqua regia respectively to remove free Sn and TiC, and finally washed three times with deionized water and dried.

[0018] Furthermore, the average diameter of the Ti2SnC nanosheets is 150-300 nm, and the average thickness is 5-10 nm.

[0019] Furthermore, the preparation method of the carbon nanotubes loaded with nano Cu particles is as follows: by weight, 1.0 to 2.5 parts of pretreated carbon nanotubes are placed in 80 to 100 parts of chemical copper plating solution, kept warm in a constant temperature water bath at 60 to 80° C. for 80 to 90 minutes, then filtered and washed three times with deionized water, and dried to obtain the carbon nanotubes loaded with nano Cu particles.

[0020] Furthermore, the preparation method of the pretreated carbon nanotubes is as follows: by weight, 3 to 6 parts of carbon nanotubes are ultrasonically cleaned in 100 parts of acetone for 2 to 4 hours, and then added to 100 parts of a sensitizing solution uniformly mixed with 100 mL of deionized water, 4 to 8 parts of 35% HCl and 2 to 5 parts of SnCl2, and then magnetic stirring is continued for 30 to 50 minutes; then 50 parts of a 1% AgNO3 aqueous solution are continued to be added, and after stirring evenly, ammonia water is slowly dripped into the solution, and the addition is stopped when the solution changes from clear to brown, thereby obtaining pretreated carbon nanotubes.

[0021] Furthermore, the preparation method of the chemical copper plating solution is as follows: 3 to 5 parts of copper sulfate pentahydrate and 5 to 8 parts of formaldehyde are added to 100 parts of deionized water in parts by weight to obtain solution A. Then, 15 to 25 parts of sodium tartrate are dissolved in 250 parts of deionized water, and then 5.0 to 6.2 parts of anhydrous sodium carbonate are added and mixed uniformly to obtain solution B. After the prepared solution A and solution B are mixed uniformly, the pH of the solution is adjusted to 12 with a supersaturated sodium hydroxide solution to obtain a chemical copper plating solution.

[0022] Furthermore, the organic acid is citric acid, glutaric acid or malic acid.

[0023] The present invention proposes a novel high-temperature resistant and highly conductive soldering technology solution, which aims to significantly improve the conductive properties and high-temperature service performance of soldering materials by carefully designing the microstructure and components of the soldering alloy. The soldering adopts a unique composite structure of an outer tin alloy and an inner core flux. Among them, the tin alloy is composed of a Sn matrix, dumbbell-shaped nano-Ag particles, Ti2SnC nanosheets, and a small amount of Cu, La, and Ce elements. At the same time, a β-Sn phase matrix is ​​formed in the alloy. A key design of the present invention is to construct a semi-coherent interface by regulating the interface structure between the Ag3Sn phase and the Ti2SnC nanosheets and the β-Sn matrix. A semi-coherent interface refers to a certain lattice matching between the two phases, and the atomic arrangement at the interface is relatively orderly. First, the Ag3Sn / β-Sn semi-coherent interface helps to improve the conductive properties of soldering. In the semi-coherent structure, the Fermi levels of the materials on both sides of the interface tend to be consistent, which is conducive to the smooth transmission of carriers between different phases. At the same time, less lattice distortion at the interface can reduce the probability of electron scattering, extend the migration path of carriers in the conductive phase, and further reduce the resistivity of the material. In addition, the Ag3Sn phase itself has a certain conductivity, and its uniform distribution is more conducive to the formation of an efficient electron transmission channel. Secondly, the Ti2SnC / β-Sn semi-coherent interface plays an important role in improving the high temperature resistance of soldering. Ti2SnC belongs to MAX phase ceramics with excellent high temperature stability and creep resistance. The introduction of Ti2SnC nanosheets into the β-Sn matrix and the special structure of the semi-coherent interface can effectively hinder dislocation movement and atomic diffusion, thereby improving the mechanical stability of soldering under high temperature environment. At the same time, the stress field existing in the semi-coherent interface can also pin the grain boundary, inhibit grain growth, maintain the fine grain strengthening effect, and thus comprehensively strengthen the soldering organization. In addition, the trace addition of Cu, La, and Ce elements is also of great significance. Cu can form intermetallic compound phases such as Cu6Sn5 with Sn, further refining the β-Sn grains. Rare earth elements such as La and Ce tend to concentrate at the grain boundaries, reducing the interface energy, improving the material's antioxidant properties, and also improving the wettability of soldering. In summary, the present invention cleverly utilizes the synergistic effect of multiple components, constructs semi-coherent interfaces of Ag3Sn / β-Sn and Ti2SnC / β-Sn, and starts from multiple aspects such as conductive phase optimization, dislocation pinning, grain refinement, and grain boundary strengthening, and finally achieves a significant improvement in soldering conductivity and high temperature resistance. This technical solution is highly scientific and has a clear mechanism, providing a new idea for the design and development of high-performance, high-temperature resistant soldering materials.

[0024] The present invention introduces dumbbell-shaped nano Ag particles into the solder alloy design, and induces the in-situ self-generation of Ag3Sn phase through high-temperature smelting to form a nano-enhanced layer with moderate thickness. This unique microstructure design significantly optimizes the comprehensive performance of the solder alloy from multiple aspects such as conductivity, high-temperature resistance and toughness. First, the conductivity of the solder alloy is significantly improved. Ag3Sn itself is an excellent conductive phase, and its uniform dispersion distribution in the Sn matrix provides more transmission channels for electrons. At the same time, the high aspect ratio of the dumbbell-shaped Ag particles is conducive to the rapid migration of electrons along the axial direction, reducing the electron scattering loss. Secondly, the solder alloy has excellent high-temperature resistance. As a hard and brittle phase, Ag3Sn has good thermal stability and creep resistance at high temperatures. Nanoscale Ag3Sn particles are dispersed in the β-Sn matrix, which can not only hinder dislocation movement and improve the yield strength of the matrix, but also pin the grain boundaries and inhibit the growth of grains at high temperatures. The semi-coherent interface between Ag3Sn and β-Sn further enhances the pinning effect, maintains the fine grain strengthening effect, and improves the microstructure stability at high temperature. In addition, the uniform stress field distribution induced by the dumbbell-shaped morphology helps to relieve local stress concentration and improve the creep resistance of the material. The synergistic effect of these mechanisms enables the solder alloy to exhibit excellent mechanical property stability under high-temperature service environment. Finally, the solder alloy also has excellent strength and toughness. By controlling the volume fraction and size of the Ag3Sn phase, its excessive growth to become a stress concentration area and crack source is avoided, and the plastic deformation ability of the matrix is ​​maintained. The nano-sizing and uniform dispersion of the Ag3Sn phase not only refines the grains of β-Sn, but also constructs a large number of semi-coherent interfaces. These heterogeneous interfaces become an effective barrier to hinder crack propagation, improving the fracture toughness of the solder alloy. At the same time, the stress field existing in the semi-coherent interface can also promote crack deflection and bifurcation, delay the rapid propagation of cracks, and further enhance the material's fracture resistance. In addition, the high specific surface area of ​​dumbbell-shaped Ag particles increases the contact area between the matrix and the reinforcement phase, strengthens the interface bonding, and improves the load transfer efficiency, thereby obtaining more excellent strength and toughness. In summary, the present invention uses dumbbell-shaped nano-Ag particles as precursors, and constructs a unique β-Sn / Ag3Sn semi-coherent heterojunction composite structure by in-situ self-generated Ag3Sn phase and regulating its size and distribution. The uniform dispersion distribution and nano-sizing of the Ag3Sn phase not only provide an efficient electron transmission channel, but also hinder dislocation movement, pin the grain boundary, and improve the yield strength and creep resistance. The presence of the semi-coherent interface reduces the interface resistance, promotes carrier transmission, and optimizes the conductive performance. At the same time, the introduced stress field inhibits crack propagation and enhances fracture toughness. In addition, the high specific surface area and aspect ratio advantages of the dumbbell-shaped morphology further strengthen electron migration and interface bonding.The coupling effect of multiple strengthening mechanisms ultimately achieves a comprehensive improvement in the conductivity, high temperature resistance and toughness of the solder alloy, providing a high-performance and highly reliable new welding material for the field of electronic packaging interconnection.

[0025] The present invention further optimizes the design of the flux on the basis of high temperature resistant and high conductivity soldering to enhance the comprehensive performance of soldering. The flux is compounded by carbon nanotubes loaded with nano Cu particles, rosin, polyvinyl alcohol and ethylene glycol, and each component plays a unique role to synergistically improve the soldering performance. First, the carbon nanotubes loaded with nano Cu particles are the key components of the flux. The carbon nanotubes have excellent electrical conductivity and thermal conductivity, and can effectively improve the heat conduction and current distribution uniformity of the flux during the welding process. At the same time, the carbon nanotubes also have extremely high specific surface area and aspect ratio, which can increase the contact area between the flux and the tin alloy, accelerate the mutual diffusion of elements, and promote metallurgical bonding. The loaded nano Cu particles further enhance the electrical conductivity of the carbon nanotubes, and can partially dissolve into the tin alloy during the welding process, and micro-alloying strengthens the soldering joint structure. Secondly, rosin, as another important component of the flux, mainly plays the role of deoxidation and wetting assistance. When heated, rosin can decompose to produce a reducing atmosphere, effectively preventing the tin alloy and the substrate from being oxidized. At the same time, the thermal decomposition products of rosin can also react with the oxides on the surface of the substrate, remove the oxide layer, reduce the tension of the welding surface, improve the spreadability and wettability of the tin alloy on the substrate surface, and help to obtain a smooth and dense welding joint. In addition, polyvinyl alcohol and ethylene glycol mainly play the role of adhesives and dispersants. Polyvinyl alcohol gives the flux good adhesion, so that it can firmly adhere to the surface of the substrate and the tin alloy, ensuring the stability and reliability of the welding process. Ethylene glycol helps to improve the dispersion of carbon nanotubes in the flux, avoid agglomeration, and play the best enhancement effect. At the same time, ethylene glycol can also adjust the viscosity and wettability of the flux and optimize the adaptability of the reflow soldering process. In summary, the above four components complement each other and play their own unique roles in the flux. Carbon nanotubes loaded with nano Cu particles significantly improve the electrical and thermal conductivity and accelerate the interface metallurgical reaction; rosin creates a reducing protective atmosphere, removes the surface oxide layer, and improves wettability; polyvinyl alcohol enhances adhesion, and ethylene glycol improves dispersion. The synergistic effect of multiple components ultimately achieves a comprehensive improvement in the performance of the flux, thereby optimizing the microstructure and mechanical properties of the solder joint and improving the welding reliability. It should be pointed out that the flux formula still maintains a relatively high rosin content, taking into account both the adaptability of the welding process and cost considerations. At the same time, the introduction of carbon nanotubes loaded with nano Cu particles and ethylene glycol gives the flux more excellent electrical and thermal conductivity and dispersibility, making up for the shortcomings of traditional rosin-based fluxes. This idea of ​​balancing performance and cost is worth learning from. In short, the present invention cleverly designs a composite flux formula with carbon nanotubes loaded with nano Cu particles as the functional phase, rosin as the matrix, and polyvinyl alcohol and ethylene glycol as auxiliary components. By giving play to the synergistic enhancement of each component, the comprehensive performance and reliability of high-temperature resistant and high-conductivity soldering are significantly improved, providing new impetus for the development of advanced electronic packaging interconnection technology.

[0026] The present invention also provides a method for preparing a high temperature resistant and highly conductive tin solder wire, comprising the following steps:

[0027] S1. Preparation of tin alloy: According to the ratio, dumbbell-shaped nano-Ag particles, Ti2SnC nanosheets, Sn powder, and Cu powder are smelted at 700-900°C for 60-90 minutes to obtain a tin alloy.

[0028] S2. Preparation of flux: First, stir the carbon nanotubes loaded with nano-Cu particles and ethylene glycol at room temperature at a speed of 300-450 r / min for 60-90 min, then add rosin and polyvinyl alcohol and heat to 120-140°C, then stir evenly at a speed of 100-200 r / min, filter while hot and collect the filtrate, and cool and solidify at room temperature to obtain the flux.

[0029] S3. Preparation of high temperature resistant and highly conductive tin solder: Add tin alloy and flux into an extruder at the same time, extrude and mold at 140-160°C to obtain high temperature resistant and highly conductive tin solder wire.

[0030] The present invention provides a method for preparing a high-temperature resistant and highly conductive tin solder wire, aiming to obtain a new tin-based solder with excellent comprehensive performance through alloy component design and flux optimization. The method mainly includes three key steps: preparing a tin alloy, preparing a flux, and preparing a tin solder wire by combining the two. Each link cooperates with each other, and finally achieves a comprehensive improvement in the conductivity, high-temperature resistance and welding process adaptability of the tin solder wire. First, in the preparation process of the tin alloy, a multi-component composite strengthening strategy is adopted. By introducing dumbbell-shaped nano-Ag particles, Ti2SnC nanosheets and nano-Cu powder into the Sn matrix, a multi-scale and multi-type heterogeneous interface is constructed. Among them, the dumbbell-shaped Ag particles generate Ag3Sn in situ during the smelting process to form a nano-Ag3Sn / β-Sn semi-coherent interface, which can not only refine the grain size of β-Sn, improve strength and toughness, but also reduce interface resistance and optimize conductive properties. Ti2SnC nanosheets, as a typical MAX phase, have the dual characteristics of "metal-like" and "ceramic-like". Dispersed distribution in the matrix can hinder dislocation movement, improve yield strength and creep resistance, and improve the electrical and thermal conductivity of the matrix. The addition of nano Cu powder not only helps to refine the primary structure, but also plays a role in solid solution strengthening. Multi-component synergistic strengthening enables the tin alloy to achieve balanced optimization in terms of mechanical and physical properties. Secondly, in the preparation of the flux, the strategy of loading Cu with carbon nanotubes was adopted. First, carbon nanotubes were mixed with ethylene glycol, and the carbon nanotubes were evenly dispersed in the solvent by the dispersing effect of ethylene glycol. Then, rosin and polyvinyl alcohol were added to form a uniform melt under heating and stirring conditions. The introduction of carbon nanotubes and Cu nanoparticles significantly improved the electrical and thermal conductivity of the flux. Cu nanoparticles can also diffuse into the weld area during welding, playing a role of microalloying. As the main component of traditional flux, rosin has good deoxidation and protection effects, which can effectively remove the oxide film on the surface of the weldment and prevent reoxidation during welding. Polyvinyl alcohol plays a viscosity-enhancing role, which can improve the adhesion and film-forming properties of the flux and improve the adaptability of the welding process. Finally, in the preparation process of the tin solder wire, an extrusion composite molding process is adopted. The prepared tin alloy and flux are mixed and extruded at 140-160°C. At this temperature, the tin alloy is in a subsolid state and has a certain plastic deformation ability, while the flux is transformed into a molten state. During the extrusion process, the molten flux can penetrate into the gaps and surfaces of the tin alloy particles to form a uniform coating layer, and the tin alloy particles undergo plastic deformation under the action of the extrusion stress, the particle gap is reduced, and the interface bonding is tighter. After extrusion and compounding, the tin alloy and the flux achieve the best match, which not only ensures the mechanical integrity of the tin solder wire, but also takes into account the full contact between the flux and the weldment and the diffusion of elements during the welding process. In short, the present invention cleverly combines the alloy composition design, flux optimization and extrusion composite molding process, starting from multiple angles, and finally prepares a high-temperature resistant and highly conductive tin solder wire with excellent comprehensive performance.The multi-component combination of alloy components has established multiple strengthening mechanisms, achieving the synergistic improvement of mechanical properties and electrical conductivity; the introduction of carbon tubes and metal nanoparticles in the flux further optimizes the electrical and thermal conductivity, and the retention of traditional flux components takes into account both deoxidation and adhesion; and the full combination of alloy and flux promotes wetting and element diffusion during welding, improving the metallurgical quality of the welded joint. This multi-level and multi-angle performance optimization strategy provides new ideas for the development of high-performance welding materials for advanced electronic packaging.

[0031] (3) Beneficial technical effects

[0032] 1. The present invention introduces dumbbell-shaped nano-Ag particles and induces the in-situ self-generation of Ag3Sn phase to form a unique β-Sn / Ag3Sn semi-coherent heterojunction composite structure, which significantly optimizes the comprehensive performance of the solder alloy. Compared with traditional solder alloys, the present invention has achieved breakthrough improvements in conductivity, high temperature resistance and toughness. In terms of conductivity, the uniform dispersion distribution of the Ag3Sn phase and the high aspect ratio of the dumbbell-shaped Ag particles provide more efficient electron transmission channels, significantly improving the conductivity. In terms of high temperature resistance, the dispersed distribution and pinning effect of the nano-Ag3Sn particles significantly improve the yield strength and creep resistance of the material. In terms of toughness, the fracture toughness of the material is improved by precisely controlling the size and distribution of the Ag3Sn phase and combining the stress field effect of the semi-coherent interface. This comprehensive improvement in performance makes the present invention have broad application prospects in high-reliability scenarios such as high-power density electronic packaging and 5G communication base stations, and is expected to solve the industry problem of insufficient reliability of existing solders in extreme service environments. The components of the present invention exhibit excellent synergy: dumbbell-shaped nano-Ag particles are used as precursors, and react with Sn through high-temperature smelting to generate uniformly dispersed nano-Ag3Sn phases, forming semi-coherent interfaces; the size and distribution of the Ag3Sn phase are precisely controlled by process parameters to provide a conductive channel while avoiding excessive growth; the stress field formed at the interface between the β-Sn matrix and the Ag3Sn phase is conducive to electron transmission and can hinder crack propagation. This multi-scale, multi-mechanism synergy enables the present invention to achieve a synergistic improvement in conductivity, high temperature resistance and toughness while maintaining good processability, breaking through the performance limitations of traditional solder alloys, and providing a high-performance, high-reliability new material solution for the field of electronic packaging interconnection.

[0033] 2. The present invention introduces Ti2SnC nanosheets and other elements into the tin-based solder to construct a Ti2SnC / β-Sn semi-coherent interface, and utilizes the synergistic effect of multiple components to comprehensively improve the high temperature resistance, electrical conductivity and comprehensive service performance of the solder material, providing a new idea for the design and development of high-performance welding materials. In the process of forming a semi-coherent interface between the Ti2SnC nanosheets and the β-Sn matrix, a certain mismatch stress field will be generated at the interface. On the one hand, this stress field can hinder the movement of dislocations and improve the yield strength and creep resistance of the material; on the other hand, it can also pin the grain boundaries, inhibit grain growth, and promote fine grain strengthening. In addition, the addition of Cu elements further refines the grains by forming an intermetallic compound phase, and La and Ce elements are segregated at the grain boundaries to improve the interface wettability and oxidation resistance. The comprehensive use of the synergistic enhancement of multiple components can significantly improve the high temperature resistance of the solder material. Compared with traditional tin-based solders, the solder material of the present invention has more stable mechanical properties in high temperature environments and significantly improved creep resistance life. This performance improvement will greatly broaden the application scenarios and working conditions adaptability of tin-based solder. For example, in the power electronic modules of new energy vehicles, the use of this material will effectively improve the reliability of solder joints and reduce interconnection losses, thereby increasing the vehicle's range; in the PCB assembly of 5G communication base stations, this material can ensure the interconnection stability of high-power devices under high temperature conditions, thereby extending the service life of the base station. In addition, the cost of this technology has increased slightly, and it is expected to achieve large-scale industrial application and drive the rapid development of industries such as electronic manufacturing, new energy, and 5G.

[0034] 3. On the basis of high temperature resistant and high conductivity soldering, the present invention further optimizes the design of the flux, and through the compounding of carbon nanotubes loaded with nano Cu particles, rosin, polyvinyl alcohol and ethylene glycol, the unique role of each component is brought into play to synergistically improve the soldering performance. Compared with the traditional rosin-based soldering flux, the soldering flux improves the conductivity while maintaining good process adaptability, and the tensile strength and shear strength of the soldering joint are significantly improved. The excellent performance of this performance is due to the synergistic effect of each component. Among them, the carbon nanotubes loaded with nano Cu particles, as the core functional phase, accelerate the element diffusion and metallurgical reaction at the soldering interface with its high electrical and thermal conductivity and unique one-dimensional nanostructure, and optimize the microstructure of the soldering joint; rosin creates a reducing protective atmosphere, removes the oxide layer on the surface of the substrate, and improves wettability; polyvinyl alcohol and ethylene glycol play the role of enhancing adhesion and improving dispersibility respectively. It is the organic combination and mutual promotion of each component that makes the performance of the soldering flux comprehensively improved, and finally achieves the significant optimization of the mechanical properties and reliability of the soldering joint. In practical applications, the flux is expected to solve the pain points in multiple fields. Taking the field of new energy vehicles as an example, on-board electronic products often work in complex environments such as high temperature, vibration, and humidity, which puts forward extremely high reliability requirements for welding interconnections. The use of the flux of the present invention can keep the shear strength of the welded joint above 30MPa after being stored at 150°C for 1000 hours, while the solder joints prepared by the traditional flux have completely failed under this condition. At the same time, in the thermal shock test, the number of heat shock resistance of the solder joints prepared by the flux reached more than 4000 times, while the conventional solder joints were only about 1500 times. Therefore, the flux is expected to greatly improve the reliability of on-board electronics and promote the development of new energy vehicles. Similarly, in the fields of 5G communications, aerospace, etc., the flux will also play an important role with its excellent high temperature resistance and conductive properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a SEM morphology image of the dumbbell-shaped nano-Ag particles prepared in Example 1 of the present invention.

[0036] Figure 2 This is the XRD phase analysis diagram of the dumbbell-shaped nano-Ag particles prepared in Example 1 of the present invention.

[0037] Figure 3 This is the SEM morphology of the Ti2SnC nanosheets prepared in Example 1 of the present invention.

[0038] Figure 4 This is the XRD phase analysis diagram of the Ti2SnC nanosheets prepared in Example 1 of the present invention.

[0039] Figure 5 This is a TEM photograph of the Ag3Sn / Sn interface prepared in Example 1 of the present invention.

[0040] Figure 6 This is a TEM photograph of the Ti2SnC / Sn interface prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0041] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0042] In the case of not specifying specific conditions, the operation in the embodiment is carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. The parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.

[0043] Table 1 Reagents required for the examples and comparative examples and the corresponding purchasing companies

[0044]

[0045]

[0046] Example 1

[0047] The utility model relates to a high temperature resistant and high conductive tin soldering wire, which is composed of a tin alloy of an outer layer and a soldering flux of an inner core.

[0048] The tin alloy is prepared from the following components as raw materials in parts by weight: 3 parts of dumbbell-shaped nano-Ag particles, 2 parts of Ti2SnC nanosheets, 80 parts of Sn powder, 1.2 parts of Cu powder, 0.001 parts of La powder and 0.002 parts of Ce powder.

[0049] The tin alloy contains Ag3Sn phase and β-Sn phase. The Ag3Sn phase is formed in situ by dumbbell-shaped nano-Ag particles and Sn powder during high-temperature smelting. The Ag3Sn phase is evenly distributed on the surface of the dumbbell-shaped nano-Ag particles with a thickness of 2nm. The Ag3Sn phase forms a semi-coherent interface with the β-Sn in the tin alloy; the Ti2SnC nanosheets form a semi-coherent interface with the β-Sn, the average length of the dumbbell-shaped nano-Ag particles is 5nm, the average diameter of the Ti2SnC nanosheets is 150nm, and the average thickness is 5nm.

[0050] The soldering flux is prepared from the following components by weight: 3 parts of carbon nanotubes loaded with nano Cu particles, 15 parts of rosin, 10 parts of polyvinyl alcohol, 4 parts of ethylene glycol, and 6 parts of citric acid.

[0051] The preparation method of dumbbell-shaped nano-Ag particles is as follows: 5 parts of 0.01mol / L AgNO3 solution and 4 parts of 0.01mol / L trisodium citrate solution are mixed evenly to form a seed solution for standby use. Then, 4 parts of 0.01mol / L sodium borohydride, 2 parts of 0.01mol / L AgNO3 and 3 parts of 0.01mol / L ascorbic acid are sequentially added into 20 parts of 0.08mol / L hexadecyltrimethylammonium bromide aqueous solution to obtain a growth solution, and then 2 parts of seed solution are added into the growth solution, and then the pH value of the growth solution is adjusted to 11 with 0.2mol / L NaOH solution, after stirring for 2h, the solution is filtered, and the filter residue is washed three times with deionized water, and then dried in a vacuum drying oven at room temperature to obtain dumbbell-shaped nano-Ag particles.

[0052] The preparation method of Ti2SnC nanosheets is as follows: by weight, the block Ti2SnC is crushed with a crusher, and then the Ti2SnC powder is obtained by ball milling and then sieved through a 500-mesh sieve, followed by washing with 25wt% HCl solution and 25wt% aqua regia once respectively to remove free Sn and TiC, and finally washed three times with deionized water and dried.

[0053] The preparation method of carbon nanotubes loaded with nano Cu particles is as follows: by weight, 1.0 parts of pretreated carbon nanotubes are placed in 80 parts of chemical copper plating solution, kept in a constant temperature water bath at 60°C for 80 minutes, then filtered and washed three times with deionized water, and dried to obtain carbon nanotubes loaded with nano Cu particles. The preparation method of pretreated carbon nanotubes is as follows: by weight, 3 parts of carbon nanotubes are ultrasonically cleaned in 100 parts of acetone for 2 hours, then added to 100 parts of a sensitizing solution uniformly mixed with 100mL deionized water, 4 parts of HCl with a mass fraction of 35%, and 2 parts of SnCl2, and then continued to stir magnetically for 30 minutes; then continued to add 50 parts of 1% AgNO3 aqueous solution, stirred evenly, slowly dripped ammonia water into the solution, and stopped adding when the solution changed from clear to brown, to obtain pretreated carbon nanotubes. The preparation method of the chemical copper plating solution is as follows: 3 parts of copper sulfate pentahydrate and 5 parts of formaldehyde are added to 100 parts of deionized water in parts by weight to obtain solution A. Then, 15 parts of sodium tartrate are dissolved in 250 parts of deionized water, and then 5.0 parts of anhydrous sodium carbonate are added and mixed uniformly to obtain solution B. After the prepared solution A and solution B are mixed uniformly, the pH of the solution is adjusted to 12 with a supersaturated sodium hydroxide solution to obtain a chemical copper plating solution.

[0054] This embodiment also provides a method for preparing a high temperature resistant and highly conductive solder wire, comprising the following steps:

[0055] S1. Preparation of tin alloy: According to the ratio, dumbbell-shaped nano-Ag particles, Ti2SnC nanosheets, Sn powder, and Cu powder are smelted at 700°C for 60 minutes to obtain a tin alloy.

[0056] S2. Preparation of flux: First, stir the carbon nanotubes loaded with nano-Cu particles and ethylene glycol at 300 r / min at room temperature for 60 min, then add rosin and polyvinyl alcohol and heat to 120°C, then stir evenly at 100 r / min, filter while hot and collect the filtrate, and cool and solidify at room temperature to obtain the flux.

[0057] S3. Preparation of high temperature resistant and highly conductive tin solder: Add tin alloy and flux into an extruder at the same time, extrude and mold at 140°C to obtain high temperature resistant and highly conductive tin solder wire.

[0058] By performing a variety of characterization analyses on the samples prepared in Example 1, the results fully confirmed the feasibility and effectiveness of the present invention. Figure 1 The SEM morphology of the successfully prepared dumbbell-shaped Ag nanoparticles clearly shows the characteristic morphology. Figure 2 XRD phase analysis further confirmed the phase composition of these nanoparticles. Figure 3 The SEM morphology shows the unique sheet structure of Ti2SnC nanosheets. Figure 4 XRD analysis verifies its phase purity. Figure 5 and Figure 6 The TEM images reveal the microstructures of the Ag3Sn / Sn and Ti2SnC / Sn interfaces, both of which show semi-coherent interface characteristics, which is of great significance for understanding the interface properties of materials. These comprehensive analysis results not only confirm the success of the present invention in the preparation of nanomaterials, but also provide an intuitive experimental basis for in-depth exploration of the interface properties of materials.

[0059] Example 2

[0060] The utility model relates to a high temperature resistant and high conductive tin soldering wire, which is composed of a tin alloy on the outer layer and a soldering flux on the inner core.

[0061] The tin alloy is prepared from the following components as raw materials in parts by weight: 4 parts of dumbbell-shaped nano-Ag particles, 3 parts of Ti2SnC nanosheets, 85 parts of Sn powder, 1.9 parts of Cu powder, 0.002 parts of La powder and 0.003 parts of Ce powder.

[0062] The tin alloy contains Ag3Sn phase and β-Sn phase. The Ag3Sn phase is formed in situ by dumbbell-shaped nano-Ag particles and Sn powder during high-temperature smelting. The Ag3Sn phase is evenly distributed on the surface of the dumbbell-shaped nano-Ag particles with a thickness of 3nm. The Ag3Sn phase forms a semi-coherent interface with the β-Sn in the tin alloy; the Ti2SnC nanosheets form a semi-coherent interface with the β-Sn, the average length of the dumbbell-shaped nano-Ag particles is 7nm, the average diameter of the Ti2SnC nanosheets is 195nm, and the average thickness is 7nm.

[0063] The soldering flux is prepared from the following components by weight: 5 parts of carbon nanotubes loaded with nano Cu particles, 18 parts of rosin, 12 parts of polyvinyl alcohol, 6 parts of ethylene glycol, and 9 parts of glutaric acid.

[0064] The preparation method of dumbbell-shaped nano-Ag particles is as follows: 7 parts of 0.01mol / L AgNO3 solution and 6 parts of 0.01mol / L trisodium citrate solution are mixed evenly to form a seed solution for standby use. Then, 6 parts of 0.01mol / L sodium borohydride, 3 parts of 0.01mol / L AgNO3 and 5 parts of 0.01mol / L ascorbic acid are sequentially added into 20 parts of 0.08mol / L hexadecyltrimethylammonium bromide aqueous solution to obtain a growth solution, and then 3 parts of seed solution are added to the growth solution, and then the pH value of the growth solution is adjusted to 11 with 0.2mol / L NaOH solution, after stirring for 3h, the solution is filtered, and the filter residue is washed three times with deionized water, and then dried in a vacuum drying oven at room temperature to obtain dumbbell-shaped nano-Ag particles.

[0065] The preparation method of Ti2SnC nanosheets is as follows: by weight, the block Ti2SnC is crushed with a crusher, and then the Ti2SnC powder is obtained by ball milling and then sieved through a 500-mesh sieve, followed by washing with 25wt% HCl solution and 25wt% aqua regia once respectively to remove free Sn and TiC, and finally washed three times with deionized water and dried.

[0066] The preparation method of carbon nanotubes loaded with nano Cu particles is as follows: by weight, 1.5 parts of pretreated carbon nanotubes are placed in 86 parts of chemical copper plating solution, kept in a constant temperature water bath at 66°C for 83 minutes, then filtered and washed three times with deionized water, and dried to obtain carbon nanotubes loaded with nano Cu particles. The preparation method of pretreated carbon nanotubes is as follows: by weight, 4 parts of carbon nanotubes are ultrasonically cleaned in 100 parts of acetone for 3 hours, then added to 100 parts of a sensitizing solution uniformly mixed with 100mL deionized water, 5 parts of HCl with a mass fraction of 35%, and 3 parts of SnCl2, and then continued to stir magnetically for 36 minutes; then continued to add 50 parts of 1% AgNO3 aqueous solution, stirred evenly, slowly dripped ammonia water into the solution, and stopped adding when the solution changed from clear to brown, to obtain pretreated carbon nanotubes. The preparation method of the chemical copper plating solution is as follows: 4 g of copper sulfate pentahydrate and 6 parts of formaldehyde are added to 100 parts of deionized water in order by weight to obtain solution A. Then, 18 parts of sodium tartrate are dissolved in 250 parts of deionized water, and then 5.4 parts of anhydrous sodium carbonate are added and mixed uniformly to obtain solution B. After the prepared solution A and solution B are mixed uniformly, the pH of the solution is adjusted to 12 with a supersaturated sodium hydroxide solution to obtain a chemical copper plating solution.

[0067] This embodiment also provides a method for preparing a high temperature resistant and highly conductive solder wire, comprising the following steps:

[0068] S1. Preparation of tin alloy: According to the ratio, dumbbell-shaped nano-Ag particles, Ti2SnC nanosheets, Sn powder, and Cu powder are smelted at 760°C for 69 minutes to obtain a tin alloy.

[0069] S2. Preparation of flux: First, the carbon nanotubes loaded with nano-Cu particles and ethylene glycol are stirred at room temperature at a speed of 345 r / min for 69 minutes, and then rosin and polyvinyl alcohol are added and the temperature is raised to 126°C, and then stirred evenly at a speed of 130 r / min. The filtrate is filtered while hot and collected, and the flux is obtained by cooling and solidifying at room temperature.

[0070] S3. Preparation of high temperature resistant and highly conductive tin solder: Add tin alloy and flux into an extruder at the same time, extrude and mold at 146°C to obtain high temperature resistant and highly conductive tin solder wire.

[0071] Example 3

[0072] The utility model relates to a high temperature resistant and high conductive tin soldering wire, which is composed of a tin alloy on the outer layer and a soldering flux on the inner core.

[0073] The tin alloy is prepared from the following components as raw materials in parts by weight: 6 parts of dumbbell-shaped nano-Ag particles, 4 parts of Ti2SnC nanosheets, 89 parts of Sn powder, 2.6 parts of Cu powder, 0.003 parts of La powder and 0.004 parts of Ce powder.

[0074] The tin alloy contains Ag3Sn phase and β-Sn phase. The Ag3Sn phase is in-situ self-generated by dumbbell-shaped nano-Ag particles and Sn powder during high-temperature smelting. The Ag3Sn phase is evenly distributed on the surface of the dumbbell-shaped nano-Ag particles with a thickness of 4nm. The Ag3Sn phase forms a semi-coherent interface with the β-Sn in the tin alloy; the Ti2SnC nanosheets form a semi-coherent interface with the β-Sn, the average length of the dumbbell-shaped nano-Ag particles is 9nm, the average diameter of the Ti2SnC nanosheets is 240nm, and the average thickness is 8nm.

[0075] The soldering flux is prepared from the following components by weight: 6 parts of carbon nanotubes loaded with nano Cu particles, 21 parts of rosin, 14 parts of polyvinyl alcohol, 7 parts of ethylene glycol, and 10 parts of malic acid.

[0076] The preparation method of dumbbell-shaped nano-Ag particles is as follows: 8 parts of 0.01mol / L AgNO3 solution and 7 parts of 0.01mol / L trisodium citrate solution are mixed evenly to form a seed solution for standby use. Then, 8 parts of 0.01mol / L sodium borohydride, 4 parts of 0.01mol / L AgNO3 and 6 parts of 0.01mol / L ascorbic acid are sequentially added into 20 parts of 0.08mol / L hexadecyltrimethylammonium bromide aqueous solution to obtain a growth solution, and then 4 parts of seed solution are added into the growth solution, and then the pH value of the growth solution is adjusted to 11 with 0.2mol / L NaOH solution, after stirring for 3h, the solution is filtered, and the filter residue is washed three times with deionized water, and then dried in a vacuum drying oven at room temperature to obtain dumbbell-shaped nano-Ag particles.

[0077] The preparation method of Ti2SnC nanosheets is as follows: by weight, the block Ti2SnC is crushed with a crusher, and then the Ti2SnC powder is obtained by ball milling and then sieved through a 500-mesh sieve, followed by washing with 25wt% HCl solution and 25wt% aqua regia once respectively to remove free Sn and TiC, and finally washed three times with deionized water and dried.

[0078] The preparation method of carbon nanotubes loaded with nano Cu particles is as follows: by weight, 1.9 parts of pretreated carbon nanotubes are placed in 92 parts of chemical copper plating solution, kept in a constant temperature water bath at 72°C for 86 minutes, then filtered and washed three times with deionized water, and dried to obtain carbon nanotubes loaded with nano Cu particles. The preparation method of pretreated carbon nanotubes is as follows: by weight, 5 parts of carbon nanotubes are ultrasonically cleaned in 100 parts of acetone for 3 hours, then added to 100 parts of a sensitizing solution uniformly mixed with 100mL deionized water, 6 parts of HCl with a mass fraction of 35%, and 4 parts of SnCl2, and then continued to stir magnetically for 42 minutes; then continued to add 50 parts of 1% AgNO3 aqueous solution, stirred evenly, slowly dripped ammonia water into the solution, and stopped adding when the solution changed from clear to brown, to obtain pretreated carbon nanotubes. The preparation method of the chemical copper plating solution is as follows: 4 parts of copper sulfate pentahydrate and 7 parts of formaldehyde are added to 100 parts of deionized water in parts by weight to obtain solution A. Then, 21 parts of sodium tartrate are dissolved in 250 parts of deionized water, and then 5.7 parts of anhydrous sodium carbonate are added and mixed uniformly to obtain solution B. After the prepared solution A and solution B are mixed uniformly, the pH of the solution is adjusted to 12 with a supersaturated sodium hydroxide solution to obtain a chemical copper plating solution.

[0079] This embodiment also provides a method for preparing a high temperature resistant and highly conductive solder wire, comprising the following steps:

[0080] S1. Preparation of tin alloy: According to the ratio, dumbbell-shaped nano-Ag particles, Ti2SnC nanosheets, Sn powder, and Cu powder are smelted at 820°C for 78 minutes to obtain a tin alloy.

[0081] S2. Preparation of flux: First, the carbon nanotubes loaded with nano-Cu particles and ethylene glycol are stirred at 390 r / min at room temperature for 78 min, then rosin and polyvinyl alcohol are added and the temperature is raised to 132°C, and then stirred evenly at 160 r / min, filtered while hot and the filtrate is collected, and cooled and solidified at room temperature to obtain the flux.

[0082] S3. Preparation of high temperature resistant and highly conductive tin solder: Add tin alloy and flux into an extruder at the same time, extrude and mold at 152°C to obtain high temperature resistant and highly conductive tin solder wire.

[0083] Example 4

[0084] The utility model relates to a high temperature resistant and high conductive tin soldering wire, which is composed of a tin alloy of an outer layer and a soldering flux of an inner core.

[0085] The tin alloy is prepared from the following components by weight: 7 parts of dumbbell-shaped nano-Ag particles, 5 parts of Ti2SnC nanosheets, 95 parts of Sn powder, 3.5 parts of Cu powder, 0.005 parts of La powder and 0.006 parts of Ce powder.

[0086] The tin alloy contains Ag3Sn phase and β-Sn phase. The Ag3Sn phase is formed in situ by dumbbell-shaped nano-Ag particles and Sn powder during high-temperature smelting. The Ag3Sn phase is evenly distributed on the surface of the dumbbell-shaped nano-Ag particles and has a thickness of 6nm. The Ag3Sn phase forms a semi-coherent interface with the β-Sn in the tin alloy; the Ti2SnC nanosheets form a semi-coherent interface with the β-Sn, the average length of the dumbbell-shaped nano-Ag particles is 12nm, the average diameter of the Ti2SnC nanosheets is 300nm, and the average thickness is 10nm.

[0087] The soldering flux is prepared from the following components by weight: 8 parts of carbon nanotubes loaded with nano Cu particles, 25 parts of rosin, 16 parts of polyvinyl alcohol, 9 parts of ethylene glycol, and 11 parts of citric acid.

[0088] The preparation method of dumbbell-shaped nano Ag particles is as follows: 10 parts of 0.01mol / L AgNO3 solution and 9 parts of 0.01mol / L trisodium citrate solution are mixed evenly to form a seed solution for standby use. Then, 10 parts of 0.01mol / L sodium borohydride, 6 parts of 0.01mol / L AgNO3 and 8 parts of 0.01mol / L ascorbic acid are sequentially added into 20 parts of 0.08mol / L hexadecyltrimethylammonium bromide aqueous solution to obtain a growth solution, and then 5 parts of seed solution are added to the growth solution, and then the pH value of the growth solution is adjusted to 11 with 0.2mol / L NaOH solution, after stirring for 4h, the solution is filtered, and the filter residue is washed three times with deionized water, and then dried in a vacuum drying oven at room temperature to obtain dumbbell-shaped nano Ag particles.

[0089] The preparation method of Ti2SnC nanosheets is as follows: by weight, the block Ti2SnC is crushed with a crusher, and then the Ti2SnC powder is obtained by ball milling and then sieved through a 500-mesh sieve, followed by washing with 25wt% HCl solution and 25wt% aqua regia once respectively to remove free Sn and TiC, and finally washed three times with deionized water and dried.

[0090] The preparation method of carbon nanotubes loaded with nano Cu particles is as follows: by weight, 2.5 parts of pretreated carbon nanotubes are placed in 100 parts of chemical copper plating solution, kept in a constant temperature water bath at 80°C for 90 minutes, then filtered and washed three times with deionized water, and dried to obtain carbon nanotubes loaded with nano Cu particles. The preparation method of pretreated carbon nanotubes is as follows: by weight, 6 parts of carbon nanotubes are ultrasonically cleaned in 100 parts of acetone for 4 hours, then added to 100 parts of a sensitizing solution uniformly mixed with 100mL deionized water, 8 parts of HCl with a mass fraction of 35%, and 5 parts of SnCl2, and then continued to stir magnetically for 50 minutes; then continued to add 50 parts of 1% AgNO3 aqueous solution, stirred evenly, slowly dripped ammonia water into the solution, and stopped adding when the solution changed from clear to brown, to obtain pretreated carbon nanotubes. The preparation method of the chemical copper plating solution is as follows: 5 parts of copper sulfate pentahydrate and 8 parts of formaldehyde are added to 100 parts of deionized water in parts by weight to obtain solution A. Then, 25 parts of sodium tartrate are dissolved in 250 parts of deionized water, and then 6.2 parts of anhydrous sodium carbonate are added and mixed uniformly to obtain solution B. After the prepared solution A and solution B are mixed uniformly, the pH of the solution is adjusted to 12 with a supersaturated sodium hydroxide solution to obtain a chemical copper plating solution.

[0091] This embodiment also provides a method for preparing a high temperature resistant and highly conductive solder wire, comprising the following steps:

[0092] S1. Preparation of tin alloy: According to the ratio, dumbbell-shaped nano-Ag particles, Ti2SnC nanosheets, Sn powder, and Cu powder are smelted at 900°C for 90 minutes to obtain a tin alloy.

[0093] S2. Preparation of flux: First, stir the carbon nanotubes loaded with nano-Cu particles and ethylene glycol at 450 r / min at room temperature for 90 min, then add rosin and polyvinyl alcohol and heat to 140°C, then stir evenly at 200 r / min, filter while hot and collect the filtrate, and cool and solidify at room temperature to obtain the flux.

[0094] S3. Preparation of high temperature resistant and highly conductive tin solder: Add tin alloy and flux into an extruder at the same time, and extrude them at 160°C to obtain high temperature resistant and highly conductive tin solder wire.

[0095] Example 5

[0096] It is basically the same as Example 1, except that the number of dumbbell-shaped nano-Ag particles used to prepare the high-temperature resistant and highly conductive tin solder wire is 7 parts.

[0097] Comparative Example 1

[0098] It is basically the same as Example 1, except that an equal amount of traditional spherical Ag particles with an average diameter of 5 nm are not added in the preparation of the high-temperature resistant and highly conductive tin solder wire.

[0099] Comparative Example 2

[0100] The method is basically the same as Example 1, except that dumbbell-shaped nano-Ag particles are not added in the preparation of the high-temperature resistant and highly conductive tin solder wire.

[0101] Comparative Example 3

[0102] It is basically the same as Example 1, except that no Ti2SnC nanosheets are added in the preparation of the high-temperature resistant and high-conductivity tin solder wire.

[0103] Comparative Example 4

[0104] The method is basically the same as Example 1, except that the carbon nanotubes loaded with nano Cu particles are replaced with an equal amount of carbon nanotubes in the preparation of the soldering flux.

[0105] Comparative Example 5

[0106] The method is basically the same as Example 1, except that the soldering flux is prepared by adding carbon nanotubes loaded with nano Cu particles.

[0107] Performance Testing

[0108] Conductivity: At 25°C, use SX1934 four-probe digital tester to test the resistivity of solder alloy. The sample surface should be clean and flat, with a thickness of ≤3mm and a size of ≥10mm×10mm. Each sample should be tested 5 times and the average value should be taken.

[0109] Wetting performance: The ability of the alloy to spread on the surface of a solid substrate after melting is tested. θ<40° is good, and <30° is excellent. The sample is a 5mm diameter, 2mm thick disc, placed on a 15mm×15mm×1mm cleaned copper plate, coated with the flux of the present invention, heated to 30-40°C above the liquid temperature in air, kept at 360°C for 10 minutes, and the contact angle is measured using AutoCAD.

[0110] Shear strength: Use DAGE-4000 multifunctional strength tester, replace the shear tool head, fix the welding sample on the shear platform, set the range to 0-100N, lift 0.05mm after touching the bottom, and the shear rate is 0.5mm / s. The test system records the displacement-shear load curve and the maximum shear force value. The test conditions are room temperature and 150℃ high temperature storage after 1000 hours.

[0111] Thermal shock resistance: The temperature cycle range of solder interconnection is 30℃ to 150℃, and the thermal shock resistance performance is judged by judging the number of thermal shocks that the interconnection can withstand before failure.

[0112] The performance of high temperature resistant and highly conductive tin solder wires of Examples 1 to 5 and Comparative Examples 1 to 5 are summarized in Table 2.

[0113] Table 2 Performance of tin solder wires of Examples 1 to 5 and Comparative Examples 1 to 5

[0114]

[0115] The main difference between Comparative Example 1 and Example 1 is that conventional spherical Ag particles are used to replace dumbbell-shaped nano-Ag particles. As can be seen from Table 2, the conductivity of Example 1 is significantly higher than that of Comparative Example 1, and the wettability is also improved. This is because the dumbbell-shaped nano-Ag particles can form a more effective conductive network and wetted interface due to their unique morphology. In terms of room temperature and high temperature shear strength and thermal shock resistance, Example 1 is slightly higher than Comparative Example 1, indicating that the dumbbell-shaped nano-Ag particles have significantly improved the mechanical properties.

[0116] The main difference between Comparative Example 2 and Example 1 is that dumbbell-shaped nano-Ag particles are not added. As can be seen from Table 2, the conductivity, wettability, room temperature and high temperature shear strength, and thermal shock resistance of Example 1 are significantly better than those of Comparative Example 2. This is because the dumbbell-shaped nano-Ag particles can not only construct an efficient conductive path, but also strengthen the matrix alloy and improve the overall mechanical properties of the solder joint.

[0117] The main difference between Comparative Example 3 and Example 1 is that no Ti2SnC nanosheets are added. As can be seen from Table 2, the room temperature and high temperature shear strength and thermal shock resistance of Example 1 are significantly higher than those of Comparative Example 3, while the conductivity and wettability are similar. This shows that Ti2SnC nanosheets mainly strengthen the second phase dispersion and hinder crack propagation, thereby greatly improving the mechanical properties and reliability of the solder joint.

[0118] The main difference between Comparative Example 4 and Example 1 is that pure carbon nanotubes are used in the flux instead of carbon nanotubes loaded with Cu nanoparticles. As can be seen from Table 2, the wetting performance of Example 1 is significantly better than that of Comparative Example 4, while other performance indicators are similar. This is because Cu nanoparticles can significantly improve the wetting effect of the flux with the molten solder and the substrate, while the carbon nanotubes mainly play the role of dispersing the Cu particles.

[0119] The main difference between Comparative Example 5 and Example 1 is that no carbon nanotubes loaded with Cu nanoparticles are added to the flux. As can be seen from Table 2, the wettability of Example 1 is better than that of Comparative Example 5, and other properties are also improved. This further confirms the key role of carbon nanotube flux loaded with Cu nanoparticles in improving the wettability and overall performance of solder joints.

[0120] By using the flux of the present invention, the shear strength of the welded joint can be maintained at more than 30 MPa after being stored at a high temperature of 150°C for 1000 hours, while the solder joints prepared by the traditional flux have completely failed under this condition. At the same time, in the thermal shock test, the number of heat shock resistance of the solder joints prepared by the flux reached more than 4000 times, while the conventional solder joints were only about 1500 times. Therefore, the flux is expected to greatly improve the reliability of vehicle-mounted electronics and promote the development of new energy vehicles. Similarly, in the fields of 5G communications, aerospace, etc., the flux will also play an important role with its excellent high temperature resistance and conductive properties.

[0121] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.

Claims

1. A high temperature resistant and highly conductive solder wire, characterized in that: It consists of a tin alloy outer layer and a flux core; The tin alloy is prepared from the following components as raw materials by weight: 3-7 parts of dumbbell-shaped nano-Ag particles, 2-5 parts of Ti2SnC nanosheets, 80-95 parts of Sn powder, 1.2-3.5 parts of Cu powder, 0.001-0.005 parts of La powder and 0.002-0.006 parts of Ce powder; The tin alloy contains Ag3Sn phase and β-Sn phase; The Ag3Sn phase is formed in situ by dumbbell-shaped nano-Ag particles and Sn powder during high-temperature smelting; The Ag3Sn phase is evenly distributed on the surface of dumbbell-shaped nano-Ag particles, with a thickness of 2-6 nm; The Ag3Sn phase forms a semi-coherent interface with the β-Sn in the tin alloy; the Ti2SnC nanosheet forms a semi-coherent interface with the β-Sn; The soldering flux is prepared from the following components by weight: 3-8 parts of carbon nanotubes loaded with nano Cu particles, 15-25 parts of rosin, 10-16 parts of polyvinyl alcohol, 4-9 parts of ethylene glycol, and 6-11 parts of organic acid.

2. A high temperature resistant and highly conductive solder wire as claimed in claim 1, characterized in that: The preparation method of the dumbbell-shaped nano-Ag particles is as follows: 5 to 10 parts of 0.01 mol / L AgNO3 solution and 4 to 9 parts of 0.01 mol / L trisodium citrate solution are uniformly mixed to form a seed solution for standby use; then 4 to 10 parts of 0.01 mol / L sodium borohydride, 2 to 6 parts of 0.01 mol / L AgNO3 and 3 to 8 parts of 0.01 mol / L ascorbic acid are sequentially added into 20 parts of 0.08 mol / L hexadecyltrimethylammonium bromide aqueous solution to obtain a growth solution; then 2 to 5 parts of the seed solution are added into the growth solution; then the pH value of the growth solution is adjusted to 11 with a 0.2 mol / L NaOH solution; after stirring for 2 to 4 hours, the solution is filtered, the filter residue is washed three times with deionized water, and then dried in a vacuum drying oven at room temperature to obtain dumbbell-shaped nano-Ag particles.

3. A high temperature resistant and highly conductive solder wire as claimed in claim 1 or 2, characterized in that: The average length of the dumbbell-shaped nano-Ag particles is 5-12 nm.

4. The high temperature resistant and highly conductive solder wire according to claim 1, characterized in that: The preparation method of the Ti2SnC nanosheets is as follows: by weight, the blocky Ti2SnC is crushed by a crusher, and then the Ti2SnC powder is obtained by ball milling and then sieved through a 500-mesh sieve, followed by washing once with a 25wt% HCl solution and 25wt% aqua regia respectively to remove free Sn and TiC, and finally washed three times with deionized water and dried.

5. A high temperature resistant and highly conductive solder wire as claimed in claim 1 or 4, characterized in that: The average diameter of the Ti2SnC nanosheets is 150-300 nm, and the average thickness is 5-10 nm.

6. The high temperature resistant and highly conductive solder wire according to claim 1, characterized in that: The preparation method of the carbon nanotubes loaded with nano Cu particles is as follows: by weight, 1.0-2.5 parts of pretreated carbon nanotubes are placed in 80-100 parts of chemical copper plating solution, kept warm in a constant temperature water bath of 60-80° C. for 80-90 minutes, then filtered and washed three times with deionized water, and dried to obtain the carbon nanotubes loaded with nano Cu particles.

7. A high temperature resistant and highly conductive solder wire as claimed in claim 6, characterized in that: The preparation method of the pretreated carbon nanotubes is as follows: by weight, 3 to 6 parts of carbon nanotubes are ultrasonically cleaned in 100 parts of acetone for 2 to 4 hours, and then added to 100 parts of a sensitizing solution uniformly mixed with 100 mL of deionized water, 4 to 8 parts of HCl with a mass fraction of 35%, and 2 to 5 parts of SnCl2, and then magnetic stirring is continued for 30 to 50 minutes; then 50 parts of a 1% AgNO3 aqueous solution are continued to be added, and after stirring evenly, ammonia water is slowly dripped into the solution, and the addition is stopped when the solution changes from clear to brown, so as to obtain pretreated carbon nanotubes.

8. The high temperature resistant and highly conductive solder wire according to claim 6, characterized in that: The preparation method of the chemical copper plating solution is as follows: by weight, 3-5 parts of copper sulfate pentahydrate and 5-8 parts of formaldehyde are added in sequence to 100 parts of deionized water to obtain solution A; then 15-25 parts of sodium tartrate are dissolved in 250 parts of deionized water, and then 5.0-6.2 parts of anhydrous sodium carbonate are added and mixed uniformly to obtain solution B; after the prepared solution A and solution B are mixed uniformly, a supersaturated sodium hydroxide solution is used to adjust the solution pH to 12 to obtain a chemical copper plating solution.

9. The high temperature resistant and highly conductive solder wire according to claim 1, characterized in that: The organic acid is citric acid, glutaric acid or malic acid.

10. A method for preparing a high temperature resistant and highly conductive solder wire according to any one of claims 1 to 9, comprising the following steps: S1. Preparation of tin alloy: According to the ratio, dumbbell-shaped nano-Ag particles, Ti2SnC nanosheets, Sn powder, and Cu powder are smelted at 700-900°C for 60-90min to obtain a tin alloy; S2. Preparation of flux: First, carbon nanotubes loaded with nano Cu particles and ethylene glycol are stirred at room temperature at a speed of 300-450 r / min for 60-90 min, then rosin and polyvinyl alcohol are added and the temperature is raised to 120-140°C, then stirred at a speed of 100-200 r / min, filtered while hot and the filtrate is collected, and cooled and solidified at room temperature to obtain flux; S3. Preparation of high temperature resistant and highly conductive tin solder: Add tin alloy and flux into the extruder at the same time, extrude and mold at 140~160℃ to obtain high temperature resistant and highly conductive tin solder wire.

Citation Information

Patent Citations

  • Nanometer Ag3Sn particle reinforced composite lead-free soldering paste and preparation method thereof

    CN104014947A

  • Ag-Cu-Ti / Sn nano-particle soldering paste and preparation method thereof

    CN104588905A